A study of the economic variable(s) driving directors' remuneration in Singapore. - Khoo, Swee Cheng. (2008)
This study seeks to shed some light on the economic driving force behind directors' remuneration in Singapore. Out study on 300 publicly listed companies in Singapore found that the domineering factor influencing directors' remuneration seems to be firm size instead of profitability in most cases.